Bishop Motiejus Valančius on persecution and education of Catholics - Tijūnėlienė, Ona (Acta Paedagogica Vilnensia, 1999)
This article describes the circumstances surrounding the publication of the book by bishop Valančius, its structure and main ideas are discussed. The book consists of a few pamphlets that were written after the ban of the Lithuanian press (1865), this book was published in Tilsit and its distribution in Lithuania was forbidden. Since the evidence was lacking Valančius has not been convicted. Some priests though were persecuted, they have been exiled to Siberia. The book, which was published again in 1929 in Kaunas, described the school and the Catholic Church in the second half of the 19th century, and the occupant’s goal to denationalize Lithuania. The realization of the objectives of the occupants took place in schools where students were denationalized, they had to accept the Orthodox faith. Served by teachers who did not know their native language, traditions ignorant. The goal of Valančius’ brochures was not only to highlight the damage inflicted upon Lithuanian people by the unacceptable education system, but also to advise how to free themselves from it, how to avoid the influence of a foreign school and its teachers..
Keywords: bishop M. Valančius; Catholic Church; education of Catholics; the Lithuanian press ban